Global Research Output of Lutetium-177 PSMA in Prostate Cancer: Bibliometric and Altmetric Analyses - Al-Rashdan, Rakan; Al-Abdallat, Haneen; Sathekge, Mike Machaba; Mirzaei, Siroos; Shahait, Mohammed; Al-Khawaldeh, Khaled; Abdlkadir, Ahmed Saad; Lee, Szeting; Al-Ibraheem, Akram (Nuklearmedizin - NuclearMedicine, 2024)
Aim The integration of innovative radio-pharmaceutical agents targeting prostate-specific membrane antigen (PSMA) within nuclear medicine has transformed prostate cancer detection and management. This study aims to investigate the present landscape of [177Lu]Lu-PSMA in prostate cancer, elucidating trends, global contributions, scholarly outlets, institutions, and thematic concentrations with an aim to inform forthcoming research endeavors.Methods We systematically probed the Scopus repository for relevant [177Lu]Lu-PSMA literature. An assessment of bibliometric and altmetric data was carried out. Finally, we assessed the correlation between the altmetric attention scores and the number of citations for the retrieved data.Results Spanning January 2015 to July 2023, the study encompassed 466 articles concerning [177Lu]Lu-PSMA therapy for prostate cancer. Predominant citation accolades gravitated towards metastatic castration-resistant prostate cancer investigations and assessments of [177Lu]Lu-PSMA therapy’s safety and efficacy. Further research encompassed adverse effects linked to [177Lu]Lu-PSMA intervention, including xerostomia, thrombocytopenia, anemia, and fatigue. Germany emerged as the primary academic contributor, with The Journal of Nuclear Medicine dominating publications (n = 55). A moderate significant correlation was detected between the number of citations and altmetric attention scores .Conclusion The findings highlight the growing interest and advancements in the utilization of [177Lu]Lu-PSMA therapy in prostate cancer and offer a comprehensive global perspective on future research directions.
Keywords: Prostate Cancer; [177Lu]Lu-PSMA; radiopharmaceuticals; nuclear medicine; Radionuclide Therapy; SPECT